Physical conditions and hormonal and ovarian profiles of hens in Trawas, Indonesia with egg laying cycle abnormalities - Prima Ayu Wibawati; Gigih Priyo Prakoso; Christina Mariantje Natal; Abzal Abdramanov (The Indian Veterinary Journal, 2025)
This study evaluated the serum FSH level and the ovarian conditions of laying hens with abnormal egg-laying cycles of 38 weeks old 46 laying hens of ISA Brown strain with interrupted egg-laying cycle on an intensive laying hens production system. Based on physical observations, it was found that the weight of laying hens with an abnormal egg-laying cycle was 1.6±0.246 kg, the comb size was small and pale red, and the pubic bone was narrow. The follicles observed follicles were primordial, small white, small yellow and post ovulatory regressing follicles, but the pre-ovulatory follicles were rarely seen. The mean value of FSH was 80.71±38.97 pg/mL. Laying hens with egg-laying cycle abnormalities were characterized by altered physical conditions, low FSH level and abnormal ovarian follicular development.